Extreme crowding in laying hens during a recurrent smothering outbreak. (19th April 2021) - Herbert, George T.; Redfearn, William D.; Brass, Elizabeth; Dalton, Hillary A.; Gill, Roger; Brass, David; Smith, Cameron; Rayner, Ann C.; Asher, Lucy
Abstract: Background: Piling, a behaviour where hens crowd together, is referred to as smothering if mortalities result. Smothering is a considerable concern for the egg industry, yet is vastly understudied. Methods: During an outbreak of recurrent smothering, continuous video footage captured a commercial, free‐range flock over 35 days. We describe the piling behaviour observed and potential associations with productivity and flock health indicators. Results: Forty‐eight piles were filmed, with a maximum density of 187.93 birds/m 2 and up to 1204 birds in one pile. Piling occurred in the same house location on 33 of 34 observation days, the first evidence of regularity in piling behaviour. Despite extreme bird densities, we did not find associations between piling extremity and productivity but did find associations with water:feed ratio and temperature range. Conclusion: This study describes the most extreme level of piling reported in literature and offers new insights into this problem behaviour and its consequences.